Renewable energy policy and initiatives in Malaysia - Lim, Chin Haw; Salleh, Elias; Jones, Philip (Faculty of Design & Architecture, Universiti Putra Malaysia, 2006)
Energy has always been an essential element for the generation of social and economic growth in a country. It is no longer viewed as a luxury as it used to be but it has become a necessity in our everyday life. Malaysia, a country located between 1° and 7° North of the Equator, has an abundance of renewable energy resources such as solar, wind, hydro and biomass but most of these renewable energy resources are not fully exploited. Presently, Malaysia is still very much dependent on fossil fuels as its primary source of energy. Due to the current upward trend of fuel prices, especially crude oil prices in the world market, the Malaysian Government is forced to look into other alternative energy sources with the emphasis on renewable energy. There are numerous efforts taken by the Malaysian Government in pursuit of the exploitation of renewable energy. This paper will discuss the five main initiatives taken by the Malaysian government on renewable energy, namely Renewable Energy as the 5th Fuel under the 8th and 9th Malaysian Plan, MS1525 or Energy Efficiency in Commercial Buildings, the Kyoto Protocol, the Malaysian Building Integrated Photovoltaic Programme, also known as MBIPV, and Biomass.